STUDI PUTUSAN MAHKAMAH AGUNG DALAM PENYELESAIAN KASUS PERDATA PELANGGARAN KONTRAK (WANPRESTASI) DI INDONESIA - , Yulia Anita Indrianingrum, Dr. Rimawan Pradiptyo, MSc. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
In this study, the researchers wanted to know what are the factors that can influence the judges of the Supreme Court to resolve a civil case for breach of contract (default) in Indonesia and want to find out how much benefit-cost of the proposed plaintiff's breach of contract. This study used data on the 2006-2011 Supreme Court decision in the case of breach of contract (default) is obtained from the MA website http://putusan.mahkamahagung.go.id. Research on the breach of contract in Indonesia begins with the filing of a lawsuit in court due to aberrant behavior such as opportunistic behavior of someone causing harm to others. The injured party can sue to demand reimbursement of expenses, damages and interest to the adverse party. This study uses the analysis of observations by the method of case control and descriptive method, yurimetri for judicial review and logistic regression for the empirical study and its benefit-cost analysis obtained by the plaintiff. From the analysis of data and research results concluded that the First, the case control and descriptive equipped with the Supreme Court decision to observe, evaluate and analyze the decision of a breach of contract in each level of court, the Second, the method can be analyzed yurimetri that there are three categories of behavior tendency of the presiding judge MA in deciding cases in favor of the trend, decided balanced (series) and decided to reject the plaintiff's claim, the Third, with empirically tested by logistic regression methods can be concluded that the position of plaintiff, plaintiff's action, the principal amount of material loss and the plaintiff's final decision in District Court statistically significantly affect the judge's ruling in the Supreme Court to grant / deny plaintiff's claim and the study completed a cost-benefit analysis concluded that the benefits obtained by the plaintiff of magnitude greater than the costs to the plaintiff but not greater than the accumulated amount of the principal substantive tort claimants per years.